An Analysis of Grammatical Errors in Writing Recount Texts by the Tenth Graders - Bella Rizky Amelia; Sri Rachmajanti; Mirjam Anugerahwati (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This study was conducted to analyze the grammatical errors in writing recount texts by the tenth graders. A table analysis and a questionnaire were being used in this study. The data was analyzed based on the surface strategy taxonomy that was adapted from Dulay, Burt, and Krashen (1982). The errors were classified into four categories; omission, addition, misformation, and misordering. The subject was 24 students. This study used a qualitative method which was a descriptive analysis. There were some instruments in this study; the writing task, the table of analysis, the questionnaire and the scoring formula. The result of this study shows that the students still made grammatical errors in writing the recount text. There are 447 errors in the students' writing. Misformation error becomes the most common error with a frequency 190 errors (42.5). Then, it was followed by 162 omission errors (36.3%), 86 addition errors (19.2%), 9 misordering errors (2.0%). The questionnaire findings indicate that most students did not understand how to apply the grammar rules in their writings and teachers need to give more explanation how to apply the grammar rules in writing. Keywords: grammatical errors, recount text, tenth graders Abstrak: Penelitian ini bertujuan untuk menganalisis kesalahan tata bahasa dalam penulisan teks recount oleh siswa kelas 10. Penelitian ini menggunakan tabel analisis dan kuesioner. Data dianalisis dengan berdasarkan surface strategy taxonomy yang dikemukakan oleh Dulay, Burt, and Krashen (1982). Kesalahan-kesalahan yang ada dibagi menjadi empat kategori; omission, addition, misformation, dan misordering. Subyek penelitian terdiri dari 24 siswa. Penelitian ini menggunakan metode kualitatif, lebih tepatnya analisis deskriptif. Instrumen yang digunakan antara lain; tugas menulis, tabel analisis, kuesioner, dan rumus skoring. Hasil penelitian menunjukkan bahwa siswa masih membuat kesalahan dalam menulis teks recount. Terdapat 477 kesalahan dalam tulisan siswa. Kesalahan misformation menjadi kesalahan yang paling umum dengan frekuensi sebanyak 190 kesalahan (42,5%), diikuti oleh kesalahan omission sebanyak 162 (36,3%), kesalahan addition sebanyak 86 (19,2%), dan kesalahan misordering sebanyak 9 (2,0%). Menurut kuesioner, kesalahan ini masih terjadi karena kebanyakan siswa masih bingung mengenai penerapan tata bahasa dalam tulisan mereka. Oleh sebab itu, guru dianjurkan untuk menjelaskan lebih jauh mengenai cara penerapan tata bahasa dalam menulis. Kata kunci: grammatical errors, recount text, siswa kelas X